KORELASI TEKANAN DARAH DENGAN NILAI AMBANG PENDENGARAN DI LINGKUNGAN BISING MESIN PADA PEKERJA PABRIK KONVEKSI - , MUHAMMADONG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Noisy work environment is a physical factor that can cause health problems such as hearing loss (auditory) and extrauditory such as psychological stress, fatigue. Noisy in a long time and can lead to a continuous decrease in hearing, and a factor of psychological and physical stressors that can affect auditory function, physiology, and blood pressure. Noisy stimulation through the sympathetic nervous mechanisms can lead to higher blood pressure by increasing total peripheral resistance and cardiac output, with repeated exposure and may continue to accelerate the development of peripheral vascular changes in vascular structure so that it can increase blood pressure. Objective The porpose of this research is to determine the correlation of blood pressure with a threshold of hearing convection factory workers. The study design was cross-sectional. Samples were taken from the workers of PT. MTG Yogyakarta exposed to 77 dB noise machine. Furthermore, the worker checked with audiometric hearing threshold of pure tone and blood pressure measurements. Data analysis using statistical test used was the Pearson correlation test if normally distributed data, whereas Spearman's correlation test, if the data are not normally distributed. Degree of confidence that is used in the study was 95 %, with a significance level of 5% (p < 0,05). Based on the correlation results showed that there was a positive relationship with the strength of the relationship between Mean Atreal Pressure (MAP) with a lower threshold of hearing air conduction at a frequency of 125 Hz right or left ear, 250 Hz right or left ear, right ear 4000 Hz, 6000 Hz right ear or the left, as well as 8000 Hz in the left ear and 4000 Hz right bone conduction garment factory workers. Intensity noise on the measurement of the frequency of 125 Hz, 250 Hz, 4000 Hz, 6000 Hz, and 8000 Hz was 26 - 40 dB. Conclusion: there is a correlation between blood pressure with a threshold of hearing on convection factory workers in Yogyakarta.